A survey of Italian and French ornamentation in organ music of the Renaissance and Baroque - Viljoen, Willem Diederik (College of Music, 2026)
The purpose of this thesis is not to give instant solutions to the problems of Italian or French ornamentation. Instead, a survey is made of the ornaments and ornament tables of the important composers, and conclusions are drawn therefrom. What is of importance, is to distinguish between those cases which are determined by fixed principles (e.g., ornament tables), founded on historical evidence, and those in which the taste and judgement of the player plays a great role. One should know how to identify those practices which are foreign or stem from a later period, and this can only be done once the performer has a knowledge of the composer, the music performed and the general practices of the period.